Implementasi Pembelajaran Problem Based Learning Berorientasi Socio-Scientific Issues untuk Meningkatkan Keterampilan Pemecahan Masalah - Oktaviana, Rina; Aurora, Zevira Fransisca; Prasetyo, Opik; Ruwaida, Ulya; Fajeriadi, Hery; Aulia, Nurul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Problem-solving skills are an essential aspect that learners must have to deal with complex problems in real life. However, various studies show that students in Indonesia still have a low level of ability in this aspect. This study aims to measure the improvement of problem-solving skills through the application of Problem-Based Learning (PBL) based on Socio-Scientific Issues (SSI) on the topic of environmental change. This study uses a pre-experimental method with a one-group pretest-posttest design involving 34 students of class XI MIPA 1 at SMAN 1 Banjarmasin for the 2025/2026 school year. Sample selection was carried out by total sampling technique. The post-test results showed that the students' problem-solving skills were in the good category, with an average of 83.15%. MANOVA's analysis produced a significance value of 0.000 (< 0.05) which confirms that SSI-based PBL has a significant influence on improving problem-solving skills while fostering students' awareness of environmental conservation efforts. The findings of this research are expected to be a practical guide for educators in designing learning that is able to foster problem-solving skills as one of the competencies of the 21st century.